The elusive nature and diagnostics of misfolded Aβ oligomers. - Cerasoli, Eleonora; Ryadnov, Maxim; Austen, Brian M. (Frontiers in Chemistry, 2015)
Amyloid-beta (Aβ) peptide oligomers are believed to be the causative agents of Alzheimer’s disease (AD). Though post-mortem examination shows that insoluble fibrils are deposited in the brains of AD patients in the form of intracellular (tangles) and extracellular (plaques) deposits, it has been observed that cognitive impairment is linked to synaptic dysfunction in the stages of the illness well before the appearance of these mature deposits. Increasing evidence suggests that the most toxic forms of Aβ are soluble low-oligomer ligands whose amounts better correlate with the extent of cognitive loss in patients than those of fibrillar insoluble forms. Therefore, these ligands hold the key to a better understanding of AD prompting the search for clearer correlations between their structure and toxicity. The importance of such correlations and their diagnostic value for the early diagnosis of AD is discussed here with a particular emphasis on the transient nature and structural plasticity of misfolded Aβ oligomers.